Pendampingan Strategi Peningkatan Kemampuan Memahami Materi Ekonomi Akuntansi Siswa Program Studi IPS MAMA 7 Banjarwati Paciran Lamongan Jawa Timur - Siswadi, Siswadi; Syaifuddin, Ahmad; Najihah, Wilda ‘Ainun (Keris: Journal of Community Engagement, 2023)
This mentoring research aims to maximize strategies for increasing the ability to understand economic material and to increase the interest of students at Madrasah Aliah Ma'arif 7 Banjarwati, Sunan Drajat Banjarwati Paciran Lamongan Islamic Boarding School foundation. The method used in this assistance is Participatory Action Research (PAR). This assistance will be carried out in the even semester of the 2022/2023 academic year. The results of this research show; MA.MA 7 Banjarwati Sunan Drajat Islamic Boarding School maximizes the increase in the ability to understand economic material by maximizing learning strategies, learning methods and teaching aids in learning by adapting appropriate material in the teaching and learning process. Meanwhile, to increase students' interest in studying MA.MA 7 Banjarwati Sunan Drajat Islamic Boarding School Banjarwati Paciran Lamongan by formulating the problems faced by students and providing motivation to students about the importance of serious study so that it can encourage students' interest in learning with the stimulus of prizes, grades for outstanding students